Pengaruh Struktur Modal, Profitabilitas, Free Cash Flow, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Devia Marlina; Harti Budi Yanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The company's goal is not only to gain profits, but is also oriented towards shareholder prosperity through increasing company value. The company's value is reflected in its share price. This research aims to determine the influence of capital structure, profitability, free cash flow, and company size on company value. This research was conducted on consumer cyclicals and consumer non-cyclicals companies that were consistently listed on the IDX for the period 2020 to 2023. There were 293 consumer cyclicals and consumer non-cyclicals companies using purposive sampling to obtain 65 companies that passed the sampling criteria. The results obtained that company size has a significant effect on company value, while capital structure, profitability, free cash flow do not have a significant effect on company value.